Multimodal Analysis Of Gender Representation In Efl Textbooks (at The Crossroads And Let’s Meet Up) - Rezki , Khadidja; Yassine, Souryana (El Omda in Linguistics and Discourse Analysis, 2024)
This paper is a corpus-based study which compares between gender representations within two EFL textbooks, used in two different contexts; that are Algeria and France. The Algerian EFL textbook is entitled ‘At the Crossroads’ and the French one is entitled ‘Let’s Meet Up’. The study highlights gender representation in the visuals of both EFL textbooks and which dimensions they communicate. Therefore, the study relies on two theoretical frameworks. First, a multimodal analysis of the textbooks’ images relying on Kress and Van Leeuwen (2006) framework grammar of the visual design. Then, Sunderland’s gender theory to identify the existing dimensions of gender representation in the both textbooks’ images. It adopts the mixed method research, to analyze the selected corpus of twenty (20) images.